2020
DOI: 10.1364/oe.377707
|View full text |Cite
|
Sign up to set email alerts
|

Research on pose estimation for stereo vision measurement system by an improved method: uncertainty weighted stereopsis pose solution method based on projection vector

Abstract: We present UWSPSM, an algorithm of uncertainty weighted stereopsis pose solution method based on the projection vector which to solve the problem of pose estimation for stereo vision measurement system based on feature points. Firstly, we use a covariance matrix to represent the direction uncertainty of feature points, and utilize projection matrix to integrate the direction uncertainty of feature points into stereo-vision pose estimation. Then, the optimal translation vector is solved based on the projection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this step, the presented algorithm extracts two types of features for classification including geometric feature and texture features from output of ROI ψtrue(finalimgtrue). One geometric feature that is histogram of oriented gradient (HOG) (Hong et al , 2020; Kazmi et al , 2020) and two texture features including local binary pattern (LBP) and Haralick features (Al-wajih and Ghazali, 2020; Cui et al , 2020) are extracted. In order to extract Haralick features, the proposed algorithm extracted 14 Haralick texture features from GLCM, which are described in Table 1.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In this step, the presented algorithm extracts two types of features for classification including geometric feature and texture features from output of ROI ψtrue(finalimgtrue). One geometric feature that is histogram of oriented gradient (HOG) (Hong et al , 2020; Kazmi et al , 2020) and two texture features including local binary pattern (LBP) and Haralick features (Al-wajih and Ghazali, 2020; Cui et al , 2020) are extracted. In order to extract Haralick features, the proposed algorithm extracted 14 Haralick texture features from GLCM, which are described in Table 1.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…e literature [6,7] uses the HOG method to extract the information of each part of the human body in the image and then uses the classical algorithm support vector machine and random forest to identify and classify. Cui et al [8] found the global optimal features from many features such as Fourier descriptors, shape context, edges, and gradients to quickly and accurately complete the backprojection process from features to three-dimensional poses. Zhang and Lu [9] used the histogram of gradient directions to restore the human pose and trained multiple local linear regressions to restore the human pose in a single frame of image.…”
Section: Introductionmentioning
confidence: 99%
“…However, input parameters other than stereo angles were not considered, which may affect the evaluation accuracy. Cui et al [27] presented an uncertainty weighted pose measurement method, in which the covariance matrix was utilized to determine the direction of the feature points' uncertainty that was integrated into the stereovision pose estimation by the projection matrix. This method improves the accuracy of pose estimation.…”
Section: Introductionmentioning
confidence: 99%